The Characterization of Electronic Noise in the Charge Transport through Single‐Molecule Junctions. Issue 3 (28th December 2020) - Yuan, Saisai; Gao, Tengyang; Cao, Wenqiang; Pan, Zhichao; Liu, Junyang; Shi, Jia; Hong, Wenjing
Abstract: With the goal of creating single‐molecule devices and integrating them into circuits, the emergence of single‐molecule electronics provides various techniques for the fabrication of single‐molecule junctions and the investigation of charge transport through such junctions. Among the techniques for characterization of charge transport through molecular junctions, electronic noise characterization is an effective strategy with which issues from molecule–electrode interfaces, mechanisms of charge transport, and changes in junction configurations are studied. Electronic noise analysis in single‐molecule junctions can be used to identify molecular conformations and even monitor reaction kinetics. This review summarizes the various types of electronic noise that have been characterized during single‐molecule electrical detection, including the functions of random telegraph signal (RTS) noise, flicker noise, shot noise, and their corresponding applications, which provide some guidelines for the future application of these techniques to problems of charge transport through single‐molecule junctions. Abstract : The electronic noise characterization is an effective strategy for studying the molecule–electrode interface issue, the actual mode of charge transport, and the configuration changes of molecular junction. Low‐frequency noise includes flicker noise and random telegraph signal noise, originating from rearrangement of gold atoms, oscillation of the coupling strength, and conformational change of molecules. The quantum discrete property of carriers generates shot noise.